2015
DOI: 10.1186/s13231-014-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet rich clots are resistant to lysis by thrombolytic therapy in a rat model of embolic stroke

Abstract: BackgroundEarly recanalization of occluded vessels in stroke is closely associated with improved clinical outcome. Microbubble-enhanced sonothrombolysis is a promising therapy to improve recanalization rates and reduce the time to recanalization. Testing any thrombolytic therapy requires a model of thromboembolic stroke, but to date these models have been highly variable with regards to clot stability. Here, we developed a model of thromboembolic stroke in rats with site-specific delivery of platelet-rich clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
0
43
0
Order By: Relevance
“…However, it is only effective in less than half of the patients that receive rt-PA. 2,3 The mechanisms underlying this so called "rt-PA-resistance" are not completely understood but previous reports indicated that RBC-dominant thrombi respond better to rt-PA than platelet-dominant thrombi. [18][19][20][21][22][23][24][25][26] Our histological findings provide new molecular insights on the composition of RBC-rich and platelet-rich thrombus material. It seems plausible that rt-PA, which promotes the degradation of fibrin, can have a direct and efficient thrombolytic effect on the RBC-rich areas in which thin fibrin is the main extracellular scaffold.…”
Section: Discussionmentioning
confidence: 80%
“…However, it is only effective in less than half of the patients that receive rt-PA. 2,3 The mechanisms underlying this so called "rt-PA-resistance" are not completely understood but previous reports indicated that RBC-dominant thrombi respond better to rt-PA than platelet-dominant thrombi. [18][19][20][21][22][23][24][25][26] Our histological findings provide new molecular insights on the composition of RBC-rich and platelet-rich thrombus material. It seems plausible that rt-PA, which promotes the degradation of fibrin, can have a direct and efficient thrombolytic effect on the RBC-rich areas in which thin fibrin is the main extracellular scaffold.…”
Section: Discussionmentioning
confidence: 80%
“…It is well known that erythrocyte-rich thrombi have a higher density than platelet-rich thrombi on NECCT 21 22. It has been claimed that erythrocyte-rich thrombi with little fibrin content are more susceptible to pharmacological23 and mechanical therapy 24. In a recent systematic review and meta-analysis, the authors concluded that patients with a mean thrombus density of 55.1±3.1 HU had a good angiographic outcome whereas those with a mean thrombus density of 48.9±1.9 HU had a poor angiographic outcome 25.…”
Section: Discussionmentioning
confidence: 99%
“…1 The exact nature of this so-called t-PA resistance is not yet fully understood, but location, size, and composition of the occluding thrombus have been reported to be important factors influencing t-PA outcome. [4][5][6][7][8] Interestingly, various studies have shown that in particular arterial platelet-rich clots are more resistant to thrombolysis with t-PA. 7,[9][10][11] Surprisingly little is known about the precise composition of human stroke clots. Nevertheless, such information is crucial for the design of novel thrombolytic strategies.…”
Section: Introductionmentioning
confidence: 99%